THE BIRTH AND RISE OF THE INTERNATIONAL COMMERCIAL COURTS IN PARIS - BOOSTING LITIGATION OR ALTERNATIVE TO ARBITRATION - Deskoski, Toni; Dokovski, Vangel; Kocev, Ljuben (Iustinianus Primus Law Faculty in Skopje, 2019)
The process of the withdrawal of the United Kingdom form the European Union is becoming more and more complicated. However, the consequences are closer than ever. With UK on the doorstep of leaving the EU, the decisions issued by its courts would no longer benefit from the recognition system provided in Regulation (EU) No 1215/2012 of the European Parliament and of the Council of 12 December 2012 on jurisdiction and the recognition and enforcement of judgments in civil and commercial matters. As a result of this, it is expected that London would no longer be seen as a primary destination for international litigants. In the awaiting of the aftermath from the Brexit, other cities and member state countries of the EU have started the race to position themselves as the next “legal hub”. While other member states have been vocal about offering alternative courts, so far France has been at the forefront of this initiative. In this text the authors will give an overview of the new the New International Chambers of the Paris Courts. Furthermore, special attention will be given to the comparison of the international commercial courts and arbitration.
Keywords: arbitration, Brussels I (bis), party autonomy, Brexit